中國大陸部分大學教育學院遭裁撤整併之研究 - 周祝瑛(Chuing Prudence Chou); 馬冀(Ji Ma) (課程研究, 2017)
In the end of year 2015, the “Double First-Rate” (DFR) plan published by Mainland China government aimed at advancing Chinese universities and subjects to reach the world-class standard. Meanwhile, some leading universities either abolished or merged their education college or Institute of higher education in order to compete for the DFR plan. This paper started with the development and change of education department from international and Taiwan perspectives, coupled with the historical development of Chinese education department before and after 1949 and the last two decade. It was found that the reason of such re-structuring among Chinese leading universities’ education college may derive from pressure of the current DFR policy orientation, unbalanced teachers supplydemand relationship, market-driven orientation and other non-rationality leadership